INCREASING THE EFFICIENCY OF WIRING HARNESS PRODUCTION USING THE RANGKED POSITIONAL WEIGHT AND LARGEST CANDIDATE RULE METHODS - Arifin , Zainul; Sukmono , Tedjo (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
In the wiring harness door production activities, the problem that occurs is the lack of achievement of the production target of 6.19% or 6.15 units in January 2023. This is caused by differences in production output at each work station or track which are not balanced resulting in an accumulation of work in progress. In making line balancing, working time measurements are carried out in each wiring harness production operation on the man power production line by using a stopwatch. The purpose of this research is to determine the optimal wiring harness production line and increase the efficiency of wiring harness production according to the company's target line efficiency. The methods used in solving this problem are the ranked positional weight method and the largest candidate rule method. From the results of the line balancing analysis using the ranked positional weight method and the largest candidate rule method, an efficiency value of 96.33% is obtained, the resulting output is 144.5 wiring haness units with 12 work stations. These results are better than before using both methods